2018
DOI: 10.1111/his.13719
|View full text |Cite
|
Sign up to set email alerts
|

Non‐urothelial carcinomas of the bladder

Abstract: Non‐urothelial carcinomas involving the bladder are uncommon and often diagnostically challenging. These carcinomas may show squamous, adenocarcinomatous or neuroendocrine features, with immunohistochemical stains aiding the diagnosis in only a subset of cases. The clinical history in non‐urothelial bladder carcinomas is important, given that the differential diagnosis often includes secondary involvement of the bladder by direct extension or metastasis from carcinomas at other sites. This paper will review no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 99 publications
(263 reference statements)
0
31
0
Order By: Relevance
“…Urinary bladder cancer (BCa) is the 10th most common malignancy cancer worldwide, with an estimated 549,393 new cases and 199,922 deaths in 2018 ( 1 ). However, non-urothelial cancers of the urinary bladder are relatively rare, accounting for only 5% of all BCa ( 2 , 3 ). Moreover, primary bladder neuroendocrine carcinoma is an extremely rare but heterogeneous variation of non-urothelial carcinoma of the urinary bladder, representing <1% of urinary bladder neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary bladder cancer (BCa) is the 10th most common malignancy cancer worldwide, with an estimated 549,393 new cases and 199,922 deaths in 2018 ( 1 ). However, non-urothelial cancers of the urinary bladder are relatively rare, accounting for only 5% of all BCa ( 2 , 3 ). Moreover, primary bladder neuroendocrine carcinoma is an extremely rare but heterogeneous variation of non-urothelial carcinoma of the urinary bladder, representing <1% of urinary bladder neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that squamous differentiation is more resistant to radiotherapy, chemotherapy, and immunotherapy and possesses the characteristics of high risk of recurrence and poor prognosis as an independent prognostic factor of UC [2,14,15]. In addition, SqCC, as the most common variant in nonurothelial carcinomas, is usually discovered and diagnosed at its advanced stage, while a considerable number of patients have lymph node metastasis in neoplasms resection [5,16]. Currently, there are limited clinical approaches for the early diagnosis and treatment of MUT.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has shown that nUC confer a worse prognosis and are more resistant to conventional treatment [ 4 ]. The differential diagnosis of pure UC (UC without divergent differentiations), UCSD, and SqCC relies not only on histopathological features, but also on sufficient precedent pathology and medical history taking [ 5 ]. Therefore, there is an urgent need to find a sensitive biological marker to identify SqCC, UC, and UCSD and evaluate the malignant degree of them.…”
Section: Introductionmentioning
confidence: 99%
“…Genuine verrucous carcinoma is a rare tumor subtype in the urinary tract [31], however, conventional well-differentiated squamous cell carcinoma with "verrucous" architectural features is a much more common event. Since the difference between them has prognostic implications their correct identification by the pathologist matters.…”
Section: Verrucous Architecturementioning
confidence: 99%